PERSIAPAN PELAKSANAAN REAKREDITASI DI 4 PUSKESMAS KOTA YOGYAKARTA - Eka Putri Rahayu; Laksono Trisnantoro; Hanevi Djasri (Journal of Health Service Management, 2020)
Background: Accreditation is conducted to improve the quality in health service. For continuous quality improvement, we need to re-measure quality standards through re-accreditation. In 2019, several primary health care in Yogyakarta city will face re-accreditation. In order to do that, preparation is needed. Preparation for the implementation of primary health care must be planned as well as possible to gain optimal results. Objective: To analyze preparation for the implementation of primary health care re-accreditation in Yogyakarta city Methods: Descriptive research using a qualitative approach design. There were 18 participants selected by purposive sampling technique. Data collection was carried out by in-depth interview, focus group discussion (FGD) and assessment checklist. Results: For Puskesmas Kotagede I, preparation for the implemen tation of primary health care re-accreditation is good but lacking in Man and Do variable. Preparation for the implementation of primary health care re-accreditation are good for both Puskesmas Mergangsan and Gondokusuman I but lack in Do variable. For Puskesmas Tegalrejo, preparation for the implementation of primary health care re-accreditation is good but lacking in Money and Man variable. Conclusion: Primary health care and the Ministry of Health have been preparing for re-accreditation process well even though several scheduled activities have been postponed due to clashes with other assignments.